2019
DOI: 10.21082/jae.v36n2.2018.149-162
|View full text |Cite
|
Sign up to set email alerts
|

Efisiensi Teknis Usaha Tani Padi Pada Sistem Tanam Jajar Legowo Di Kabupaten Lamongan, Provinsi Jawa Timur

Abstract: Jajar Legowo planting system is one of the most recent technological innovation breakthroughs promoted by the Indonesian Government to increase rice farming productivity. Lamongan Regency, as a rice producing center in East Java Province, is one of the government's targets in developing jajar legowo planting system. However, this technology is still not yet widely implemented by farmers. The existence of new technology is thought to affect the level of technical efficiency of farmers because it can affect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
3
0
2
Order By: Relevance
“…On the other hand, a positive sign on the inefficiency parameter of the frontier processing results indicates that the variable increases technical inefficiency or means decreasing technical efficiency (Nahraeni, 2012). Cendrawasih et al (2018) confirmed the same thing, namely that the variable has a negative sign which indicates that the variable has a positive effect in increasing the level of technical efficiency.…”
Section: Factors Causing Technical Inefficiency In Rice Farmingmentioning
confidence: 56%
“…On the other hand, a positive sign on the inefficiency parameter of the frontier processing results indicates that the variable increases technical inefficiency or means decreasing technical efficiency (Nahraeni, 2012). Cendrawasih et al (2018) confirmed the same thing, namely that the variable has a negative sign which indicates that the variable has a positive effect in increasing the level of technical efficiency.…”
Section: Factors Causing Technical Inefficiency In Rice Farmingmentioning
confidence: 56%
“…Then, another empirical fact, Saketa et al (2018); Usman & Juliyani (2018) in their study revealed that land area affects the amount of rice production, so that the addition of arable land area is always accompanied by an increase in rice production. This implies that the land area factor should be a major concern for the government in order to boost rice production (Cendrawasih et al, 2019). Furthermore, in Table 2 it can also be seen that the Seed Variable also has a significant positive effect on rice production with a regression coefficient of 0.238.…”
Section: Results and Discussion The Effect Of The Application Of Prod...mentioning
confidence: 92%
“…Therefore, there should be a specific measure of efficiency, namely the maximum ability to produce output using certain inputs and technology levels (Iqbal, 2019). One of the methods commonly used to measure efficiency is the frontier production function approach (Cendrawasih et al, 2018) (Wang, 2019). It is a function that describes the maximum output that can be achieved from each level of input use (Coelli et al, 1998).…”
Section: Harvested Areamentioning
confidence: 99%